Degradation of Homestead Hollow at the InSight Landing Site Based on the Distribution and Properties of Local Deposits. Issue 4 (19th April 2020) - Grant, John A.; Warner, Nicholas H.; Weitz, Catherine M.; Golombek, Matthew P.; Wilson, Sharon A.; Baker, Mariah; Hauber, Ernst; Ansan, Veronique; Charalambous, Constantinos; Williams, Nathan; Calef, Fred; Pike, W. Thomas; et al.
Abstract: The InSight mission landed its scientific payload in Homestead hollow, a quasi‐circular depression interpreted to be a highly degraded impact crater that is 27 m in diameter. The original pristine crater formed in a preexisting impact‐generated regolith averaging ~3 m thick and the surrounding ejecta deposit, consisting of coarse and mostly fine fragments, was in disequilibrium with local geomorphic thresholds. As a result, early, relatively rapid degradation by mostly eolian, and lesser impact processes and mass‐wasting, stripped the rim and mostly infilled the hollow where sediments were sequestered. Early, faster degradation during the first ~0.1 Ga was followed by much slower degradation over the bulk of the 0.4–0.7 Ga history of the crater. Pulses of much lesser degradation are attributed to impacts in and nearby the hollow, which emplaced some rocks as ejecta and provided small inventories of fine sediments for limited additional infilling. Even lesser sediments were derived from the very slow production of fines via weathering of resistant basaltic rocks. Nevertheless, indurated regolith caps the sediment fill within the hollow and creates a relatively stable present‐day surface that further sequesters infilling sediments from remobilization. The degradation sequence at Homestead hollow is like that established at the Spirit rover landing site in Gusev crater and points to the importance of eolian, and lesser impact and mass‐wasting processes, in degrading volcanic surfaces on Mars over the past ~1 Ga. Plain Language Summary: The InSight mission landed in a highly degraded impact crater dubbed Homestead hollow in Elysium Planitia on Mars. The hollow interior is quite flat and smooth, and mostly infilled by fine‐grained sediments. Rocks are 2–3 times more numerous on the western side dubbed Rocky Field . The hollow lacks a raised rim but is marked by an increase in larger rocks. The distribution of windblown and impact materials within, around, and local to the hollow indicate degradation was mostly by wind stripping of fines from the rim and depositing them inside the hollow, with lesser contributions from impact and mass wasting processes. Rocky Field was likely formed by emplacement of ejecta during a nearby impact event occurring relatively soon after Homestead hollow formed. Most degradation occurred during the first ~0.1 Ga after hollow formation. Limited modification over most of hollow history was associated with small pulses of infilling and rock emplacement during/following nearby impact events and very slow weathering of basaltic rocks. Degradation at Homestead hollow is similar to the modification of small craters at the Spirit landing site in Gusev crater, which shows common geomorphic processes occurred on comparable surfaces in different places on Mars during the last ~1 Ga. Key Points: Homestead hollow is a degraded impact crater that was modified by mostly eolian and lesser impact and mass‐wasting processes Rocks on the western side of the hollow are ejecta emplaced during the formation of a nearby crater relatively early in hollow history Most hollow degradation occurred during the first ~0.1 Ga after formation, followed by limited exterior stripping and interior infilling